LEGAL PROTECTION AGAINST WORKERS IN WORK AGREEMENT ON OUTSOURCING SYSTEM IN INDONESIA - Shalihah, Fithriatus (Faculty of Law, Universitas Sebelas Maret, 2017)
In an outsourcing system, it is certain that the working relationship between employer and worker is a working relationship with a particular Time Agreement. This status becomes a problem because there is no certainty about the continuity of the employment relationships and the non-fulfillment of the rights that workers should receive, thus this is harming the workers economically and socially. The regulation related to the outsourcing system that stated in the Manpower Act No. 13 of 2003 is also difficult to implement in a business world since the existing rules do not meet the needs of the labor market. Company does not make the flow of production activities so that it is unclear and no legal certainty about the nature and types of core business and non core business activities. In the implementation of job protection and work requirements for outsourced workers, the government should enhance its role in the supervision and enforcement of labor law through the quantity and quality of labor inspectors.